Evaluation of 976 nm Multimode Single Emitter Laser Diodes for Efficient Pumping of 100 W+ Yb-doped Fiber Laser - Sharma, Rishi Kant; Wadhwa, Shammi; Verma, N.K.; Reddy, M.N.; Rana, H (Defence Science Journal, 2016)
Experimental evaluation of spectral and power-current (P-I) characteristics of fiber coupled single emitter multimode laser diodes used for development of efficient pumping assembly is reported. Fiber coupled laser diodes emitting around 976 nm are best suited for pumping Yb-doped fiber lasers because of excellent coupling efficiency and reduced thermal load. We have experimentally investigated emission spectrum of fiber coupled multimode laser diodes at different temperatures and drive currents. It is found that peak emission wavelength shifts towards the longer wavelength with increase in temperature and drive current. P-I characteristics of fiber coupled laser diodes have been obtained and presented for drive current from 0.4 A to 11.5 A. Based on experiment, we have constructed spectrally matched laser diode assembly for efficient pumping of 100 W fiber laser. It requires very precise control of temperature and drive current to maintain the emission spectrum. Total 162 W power is pumped in to the Yb-doped fiber laser cavity through multi-mode pump combiners and we have obtained 110 W fiber laser output power @1070 nm. The achieved optical-to-optical efficiency is 68 per cent.